Decolonizing The Future: What Does Frank Herbert’s Dune (1965) Teach Us About Colonization? - Ribeiro , Luis Felipe Dias (RCMOS - Revista Científica Multidisciplinar O Saber, 2025)
This paper looks forward to analyzing the decolonization process in Frank Herbert’s science fiction novel Dune ([1965] 2016), and as a central focus, the storyline that follows the protagonist Paul Atreides and the native population from the planet Arrakis, the Fremen. For this purpose, we used as a theoretical framework the first chapter from the book Science Fiction, Imperialism and the Third World: Essays on Postcolonial Literature and Film (2010), which is entitled Postcolonial Science Fiction: The Desert Planet (2010), by scholar Gerald Gaylard. Our analysis also incorporated key insights from Frantz Fanon’s The Wretched of the Earth ([1961] 2005), a foundational text for understanding the decolonization process. Building upon the insightful analyses of Gaylard and Fanon, this paper explores a post-colonial literary perspective, departing from conventional examinations of colonizer-colonized dynamics. The concluding section offers a reflection on the implications of colonization and the potential for decolonization within both fictional narratives and the broader global context.